2004
DOI: 10.1007/s00280-003-0752-3
|View full text |Cite
|
Sign up to set email alerts
|

Carboplatin and docetaxel in advanced non-small-cell lung cancer: results of a multicenter phase II study

Abstract: The combination of carboplatin plus docetaxel is well tolerated and is effective for the treatment of patients with previously untreated advanced or metastatic non-small-cell lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…9,29 Numerous studies have demonstrated acceptable rates of OS times (10 -15 months) and good tolerability in chemonaïve patients with advanced NSCLC who were treated with Doc/Carb. [12][13][14][15][16][17]19 In this study of patients with nonsquamous cell carcinoma, the median OS with Doc/Carb was comparable with these previous studies (14.7 months). However, the current study was not sufficiently powered to determine whether there were significant differences in median OS, and the HR for median OS between Pem/Carb-and Doc/Carb-treated patients was not statistically significant (adjusted HR ϭ 0.93, p ϭ 0.698).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…9,29 Numerous studies have demonstrated acceptable rates of OS times (10 -15 months) and good tolerability in chemonaïve patients with advanced NSCLC who were treated with Doc/Carb. [12][13][14][15][16][17]19 In this study of patients with nonsquamous cell carcinoma, the median OS with Doc/Carb was comparable with these previous studies (14.7 months). However, the current study was not sufficiently powered to determine whether there were significant differences in median OS, and the HR for median OS between Pem/Carb-and Doc/Carb-treated patients was not statistically significant (adjusted HR ϭ 0.93, p ϭ 0.698).…”
Section: Discussionsupporting
confidence: 86%
“…Although docetaxel/carboplatin (Doc/Carb) is a wellaccepted first-line option for patients with advanced NSCLC, [12][13][14][15][16][17][18][19][20] relatively few studies have assessed first-line treatment with pemetrexed/carboplatin (Pem/Carb), particularly in patients with advanced, nonsquamous NSCLC. [21][22][23][24][25] Moreover, no phase 3 randomized controlled studies have been conducted to directly compare Pem/Carb with Doc/Carb or any platinum/taxane combination as first-line treatment for patients with nonsquamous NSCLC.…”
mentioning
confidence: 99%
“…The combination of docetaxel with carboplatin has been tested successfully in various phase II studies conducted over the last 3 years [18,19,20,21,22]. Moreover, the combination docetaxel-carboplatin has demonstrated the best therapeutic index in the recent TAX326 randomized multi-institutional trial in advanced (IIIB/IV) NSCLC comparing docetaxel-carboplatin with vinorelbine-cisplatin and paclitaxel-carboplatin [23].…”
Section: Discussionmentioning
confidence: 99%
“…The principal toxicities in the above phase I studies were: neutropenia which was the main DLT of the regimen, with grade 3/4 neutropenia occurring in 14% of cycles, a 5% incidence of FN with no associated septic death, uncommon grade 3/4 thrombocytopenia (2%), grade 3/4 diarrhea in 14% of patients, whilst neurotoxicity, fatigue and mucositis were extremely rare. Overall, 5 phase II studies evaluating the docetaxel-carboplatin combination have been conducted in advanced (stage IIIB/IV) NSCLC with doses of docetaxel ranging from 60 to 100 mg/m 2 and carboplatin AUC = 5 or 6 [18,19,20,21,22]. Overall RRs have ranged from 16–39%, TTP from 5.5 to 7 months, median OS from 9 to 13.9 months, and 1-year survival from 44 to 53%.…”
Section: Discussionmentioning
confidence: 99%
“…This formula is widely used in the treatment of several type of carcinoma. [23][24][25][26][27] Although it is generally considered that creatinine clearance does not accurately reflect the glomerular filtration rate, 11,12) creatinine clearance is frequently used instead because of the inconvenience of measuring the glomerular filtration rate directly. Actually, some reported an arrangement of Calvert's formula using creatinine clearance.…”
Section: Discussionmentioning
confidence: 99%